Repair Protocol of Porcelain Laminate Veneers Through Reattachment of the Fractured Ceramic Piece: A Technical Report - Dulundu, Elif; Bilir, Halenur; Karaosmanoglu, Duygu; Özcan, Mutlu (Brazilian Dental Science, 2020)
This technical report has been developed to repair the ceramic laminate veneer without removing after fracture. The bonding between the tooth and the laminate veneer is very strict, thus removing the restoration is difficult. The disadvantages such as the loss of tissue from the tooth, the cost and time loss are eliminated with this technique. In this technical report, the cementation of porcelain to porcelain in the presence of the fractured piece is explained step by step.KeywordsCeramic; Laminate veneers; Repair.